Effect of service quality dimensions on customer satisfaction at the Nikisa Body Repair Workshop in Malang - Ardhi Ramadhani (Digital Business: Tren Bisnis Masa Depan, 2021)
This type of research is explanatory research, namely explaining the relationship between research variables and testing the hypotheses that have been formulated previously. The background for taking the title in this study is the fairly tight competition in the four-wheeled vehicle maintenance service business, which causes the NIKISA BODY REPAIR workshop to have an advantage in winning the competition. Excellence can be realized, one of which is by improving the quality of service from the NIKISA BODY REPAIR workshop so that consumer satisfaction can be realized. The purpose of this study was to determine the effect of service quality dimensions on customer satisfaction at NIKISA BODY REPAIR workshops, and to determine which service quality dimension factors most dominantly influence satisfaction at NIKISA BODY REPAIR workshops in Malang. The research method used was a sample population by distributing questionnaires to predetermined respondents (purposive sampling) to obtain research data. The data analysis used is using statistical methods such as multiple linear regression, F test, t test, to test the determined hypothesis. Based on the theoretical study used, the authors draw a hypothesis. Hypothesis I where there is significant influence simultaneously and partially between service quality dimension variables such as Physical Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X3), and Empathy (X5) to customer satisfaction variables (Y1). And the second hypothesis is suspected that the empathy variable (X5) has a dominant influence on the Customer Satisfaction variable (Y1) compared to the other four variables. From the processed data, the resulting variable dimensions of service quality have a significant effect on customer satisfaction either partially or simultaneously. And the variable dimension of service quality that has a dominant influence on customer satisfaction is the variable Empathy (X5).